Development of multiform ventricular tachycardia during atrioventricular nodal reentrant tachycardia. Issue 3 (September 1989) - Bennett, D H; Coyle, C
Abstract : A woman of 18 presented with a supraventricular tachycardia, subsequently shown to be caused by atrioventricular nodal reentry, which abruptly deteriorated to a multiform ventricular tachycardia. She had not received any antiarrhythmic drugs nor did she have any of the disorders that are usually associated with this atypical ventricular tachycardia.